Neuromodulation complementary to physiotherapy in fibromyalgia and its electroencephalographic correlates: a randomized clinical trial protocol (Research, Society and Development, 2020)
The objective of the present research is to present a protocol for a randomized, placebo-controlled triple-blind clinical trial, which will evaluate the effects of neuromodulation with transcranial direct current stimulation (tDCS) associated with physiotherapy treatment in fibromyalgia and its electroencephalographic correlates. The volunteers will be women diagnosed with fibromyalgia for at least three months, aged between 40 and 55 years. Participants will be randomly assigned to three groups: Group 1, with anodic stimulation in the left motor cortex and cathodic stimulation in the right supraorbital region; Group 2, with anodic stimulation in the left dorsolateral prefrontal cortex and cathodic stimulation in the right supraorbital region; and Group 3, with simulated type stimulation (sham). All groups will be accompanied by physiotherapy treatment. The primary outcomes will be the variations in pain, anxiety and depression levels, resulting from neuromodulation, as assessed by the Visual Analogue Scale and Beck's Anxiety and Depression Inventories, respectively. The secondary outcome will be the evaluation of the cortical electrical activity as registered by a 32-channel electroencephalogram. In data analysis, a mixed ANOVA will be used, with 3 groups of participants versus 2 moments of evaluation, with a level of significance of p